Estimation of the riverine input of organic ultraviolet filters (OUVFs) from the Pearl River Estuary to the South China Sea during the early Covid-19 pandemic - Sun, Jiaji; Lin, Huiju; Lu, Yichun; Ruan, Yuefei; Lam, Jason C.H.; Lam, Paul K.S.; Wang, Tieyu; Khim, Jong Seong; He, Yuhe (The Science of the total environment, 2024)
Organic ultraviolet filters (OUVFs) are functional ingredients used in cosmetics to protect skin from the harmful effects of ultraviolet (UV) radiation. This study presents recent findings on the distribution of OUVFs in the Pearl River Estuary (PRE), located in southern China. This investigation was conducted during the early stages of the Covid-19 pandemic when the stay-at-home policy was implemented. Analysis revealed the presence of OUVFs in both the surface and bottom water samples collected from eight major outlets of the Pearl River. The OUVFs were detected in both the dissolved phase and suspended particulate matter, with a total concentration ranging from 7.19 ± 6.54 to 20.5 ± 9.62 ng/L. Notably, OUVFs' concentrations in the study period were significantly lower compared to those reported before the pandemic. This implies that effective reduction of OUVF emissions can be achieved through usage reduction combined with the management of direct discharge and appropriate treatment by urban wastewater treatment facilities. During the study period, the annual release of OUVFs was approximately 12.6 kg/1000 people/year, with the greatest contribution from the Hu Men outlet. Consequently, it is imperative to consider the potential ecological risks associated with the release of OUVFs from the PRE into the marine environment, particularly with the potential for an accompanying rebound in risk upon the lifting of restrictions on outdoor activities in the post Covid-19 time. [Display omitted] •OUVFs emissions significantly decreased during the Covid-19 community lockdown.•OUVFs' flux was estimated to be 12.6 kg/1000 people/year from the PRD to the SCS.•EHMC and 4-MBC were two primary OUVF contaminants in the PRE region.•OUVFs with high logKow should gain more attention after outdoor restriction lifted.